The role of linguistic biases in word learning - Sia, Ming Yean (2019)
Children tend to look at name-unknownobjects when they hearnovel words, a behaviour that researchers have described through the Mutual Exclusivity (ME)constraint; that childrenstart to learn meanings of wordswith the assumption that each object has only one name. The application of the MEconstrainthas been suggested to facilitate word-learning processes. Yet, other researchers argue that childrenassociate novel labels with multiple objects, resulting in the formation of a hierarchy of word-object associations, resolving referential ambiguity across situation using aCross-situational Statistical Learningstrategy. To reconcile these two theories, the current thesisused a typical ME paradigm to test whether children are able to associate a novel label with multiple objects. Results from monolinguals suggested that children were able to map a novel labelto a name-knownobject, contrary to theone-to-one assumption between word-object associationsof theME constraint. Results from bilinguals suggested that they, too, performed in a similar manner as monolinguals. AsWoodward and Markman (1991) argued thatthe ME constraint can be overcome by other linguistic cues,the current thesistested whethersyntactic cues arealso taken into account alongside with the ME constraint when children are forming new word-object associations.It was demonstrated that children do take syntaxinto account when selectingareferent for anovel label. Furthermore, the current thesisrevealed that children were more likely to map a novel label to a name-known object if the syntax was congruence with the name-known object but not the name-unknown object. In sum, the current studies suggest that novelty preference during word-object associations should not be taken as evidence that associations between novel labels and name-known objects have not taken place. In contrast, word-object associations are likely to be non-selective;that is, children do not strictly map a novel label to one name-unknown object. Other linguistic cues also play a role during the formation ofword-object associations.